2010
DOI: 10.1089/cyber.2009.0224
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-Based Self-Help Treatment for Fear of Public Speaking: A Controlled Trial

Abstract: This study offers data about the efficacy of "Talk to Me," an Internet-based telepsychology program for the treatment of fear of public speaking that includes the most active components in cognitive-behavior therapy (CBT) for social phobia (exposure and cognitive therapies). One hundred twenty-seven participants with social phobia were randomly assigned to three experimental conditions: (a) an Internet-based self-administered program; (b) the same program applied by a therapist; (c) a waiting-list control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 70 publications
4
102
0
17
Order By: Relevance
“…En concreto, Internet ofrece un nuevo modo de dispensar tratamientos cognitivo-conductuales (tcc) (Andersson, 2009) y ha demostrado ser una intervención eficaz y de bajo coste para los trastornos de ansiedad y los trastornos del estado de ánimo (Botella, Hoffman y Moscovitch, 2004;Cuijpers y Schuurmans, 2007;Botella et al, 2010;Botella, Quero et al, 2008). Una ventaja fundamental de estos programas es que reducen el tiempo de contacto entre paciente y clínico, además de llegar a pacientes que no recibirían tratamiento de otro modo (Bauer, Golkaramnay y Kordy, 2005).…”
Section: Se Comenten Actos Ilegales Para Financiar El Juegounclassified
“…En concreto, Internet ofrece un nuevo modo de dispensar tratamientos cognitivo-conductuales (tcc) (Andersson, 2009) y ha demostrado ser una intervención eficaz y de bajo coste para los trastornos de ansiedad y los trastornos del estado de ánimo (Botella, Hoffman y Moscovitch, 2004;Cuijpers y Schuurmans, 2007;Botella et al, 2010;Botella, Quero et al, 2008). Una ventaja fundamental de estos programas es que reducen el tiempo de contacto entre paciente y clínico, además de llegar a pacientes que no recibirían tratamiento de otro modo (Bauer, Golkaramnay y Kordy, 2005).…”
Section: Se Comenten Actos Ilegales Para Financiar El Juegounclassified
“…A substantial number of trials have reported the effectiveness of disorder-specifi c iPT at treating several common mental disorders. For example, more than 10 randomised controlled trials (RCTs) have reported the clinical benefi ts of iPT for clinical and subclinical depression Perini, Titov, & Andrews, 2009;Ruwaard et al, 2009;Titov, Andrews, Davies, et al, 2010), social phobia (Andersson et al, 2006;Berger, Hohl, & Caspar, 2009;Botella et al, 2010;Carlbring et al, 2007;, and panic disorder Klein et al, 2009;Wims, Titov, Andrews, & Choi, 2010). Encouraging evidence has also been found from a smaller but rapidly growing number of RCTs or open trials evaluating iPT for generalised anxiety disorder Robinson et al, 2010;, obsessive compulsive disorder Andersson et al, 2012;Wootton et al, 2011), and post-traumatic stress disorder (Klein et al, 2010;Spence et al, 2011).…”
Section: Internet-delivered Psychological Interventionsmentioning
confidence: 99%
“…Furthermore, a variety of research has been conducted on technology-aided interventions such as online-based self-administered interventions, and promising results concerning anxiety and stress reduction have been reported (36). Selfadministered treatment programs provide cognitive-behavioural therapy (CBT) with minimal therapist support, but effective outcomes (37,38). These programs lack game plays and reward systems, they are not games per definition.…”
Section: Positive Effects Of Virtual Reality and Digital Gamesmentioning
confidence: 99%